2018
DOI: 10.3233/ch-189129
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressor support vs. liberal fluid administration in deep inferior epigastric perforator (DIEP) free flap breast reconstruction – a randomized controlled trial

Abstract: The results of this prospective interventional trial could not detect any negative impact of vasopressors, neither for the primary endpoint of flap survival nor for the overall patient outcome. The fear of vasopressor associated flap complications has led to a traditional liberal fluid administration, which failed to demonstrate any benefits when compared to a fluid restrictive vasopressor strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…A variety of defects were reconstructed, most commonly of the head and neck 13,15,16,[19][20][21][22][23][24]26 and breast. 14,16,18,23,25,27 Most studies reported no significant association between vasopressor use and the outcome measures of this study. Isolated studies found increased pedicle thrombosis with postoperative vasopressor use (OR: 3.40, p < 0.05) 22 and increased flap-related complications with intraoperative vasopressor use (OR: 1.67, p < 0.01).…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…A variety of defects were reconstructed, most commonly of the head and neck 13,15,16,[19][20][21][22][23][24]26 and breast. 14,16,18,23,25,27 Most studies reported no significant association between vasopressor use and the outcome measures of this study. Isolated studies found increased pedicle thrombosis with postoperative vasopressor use (OR: 3.40, p < 0.05) 22 and increased flap-related complications with intraoperative vasopressor use (OR: 1.67, p < 0.01).…”
Section: Resultsmentioning
confidence: 57%
“…Alpha-1 and β2 receptors found on vascular smooth muscle mediate peripheral vasoconstriction and vasodilatation, respectively. 37 Alpha-2 receptor activation 18 Chen et al 2010 14 Fang et al 2018 16 Nelson et al 2017 25 41/2527 (1. 18 Fang et al 2018 16 Nelson 19 Fang et al 2018 16 Farquhar et al 2018 20 Harris et al 2012 15 Monroe et al 2010 13 Monroe et al 2011 24 Rose Chan et al 2013 19 Fang et al 2018 16 Monroe et al 2010 13 Monroe et al 2011 24 98/2947 (3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ein kürzerer Krankenhausaufenthalt steigert das subjektive Wohlbefinden, senkt das Risiko für nosokomiale Infektionen (e. g. Wundinfektion, Harnwegsinfekte) sowie die Behandlungskosten [15,16]. Im Sinne des Fast-Track-Konzeptes begünstigt eine Senkung der stationären Verweildauer die postoperative Rehabilitation und Morbidität nachweislich [17][18][19].…”
Section: Diskussionunclassified